Micronucleus Test of DHU001, a Polyherbal Formula, in Bone Marrow Cells of Male ICR Mice - Roh, Seong-Soo (Toxicol Res, 2009)
The genotoxic effects of DHU001, a polyherbal formula were evaluated using the mouse micronucleus test. DHU001 was administered once a day for 2 continuous days by oral gavage to male ICR mice at doses of 2000, 1000 and 500 mg/kg. Cyclophosphamide was used as a known geno-toxic agent in a positive control. The appearance of a micronucleus is used as an index for genotoxic potential. In addition, the changes on the total white blood cells and differential counts on the lymphocytes, neutrophils, eosinophils, basophils and monocytes in the prepared blood smears were also conducted to observe the possible immunosuppression. The results indicats that DHU001 showed no genotoxicity effects up to 2000 mg/kg dosing levels and did not influenced on the total white blood cells and differential counts. In addition, it is also considered that there were no problems from cytotoxicity of DHU001 tested in this study because the polychromatic erythrocyte ratio was detected as > 0.41 in all tested groups.